PENGUNGKAPAN LAPORAN KEUANGAN PEMERINTAH DAERAH DI INDONESIA: SUATU TINJAUAN EMPIRIS - Rianti Kusuma (2021)
This research aims to examine the level of mandatory disclosure in local government financial reports with influencing factors, namely Legislatif Size, local government budget expenditure, Audit Finding, and Local Government Size. The population in this study is all local government financial reports in Indonesia. Sampling consisted of 111 local governments in the island of Java based on the purposive sampling method with the criteria for financial statements that have been audited by the Financial Audit Board in 2019. Testing the hypothesis in this study using Multiple Regression Analysis with the SPSS Version 25 program. The results of this study indicate that Legislatif Size has an effect significant positive on the disclosure of financial statements. Local government budget expenditure, Audit Finding, and Local Government Size have no effect on disclosure of financial statements.